Efektivitas Pembelajaran Daring Pada Mata Kuliah Bahasa Inggris Di Masa Covid 19 Dalam Meningkatkan Kemampuan Mahasiswa Jurusan Teknik Mesin STTI Bontang - Irianto; Armiyanto, Eko (BEduManagers Journal : Borneo Educational Management and Research Journal, 2021)
During the current Covid-19 pandemic, schools are required to carry out distance learning. This learning is carried out using online learning media such as E-learning, Google Classroom, Zoom, and others. The objectives of this study are (1) to add insight into the patterns of distance learning during the Covid-19 pandemic, (2) to find out the problems in distance learning during the Covid-19 pandemic, (3) to know the methods or alternative learning assessments, especially in courses English. This article was prepared using a quantitative method by collecting data through observation and interviews. The effect of doing distance learning raises many obstacles that hinder the process of teaching and learning activities. The results of the study show that not all students are ready to take part in distance learning. Starting from media that is less supportive, there is still minimal internet network and uneven quota assistance from the government. As a result of the ineffectiveness of distance learning during the Covid-19 pandemic, students did not understand the learning material provided by educators.